TEACHING ENGLISH FOR YOUNG LEARNERS USING A TOTAL PHYSICAL RESPONSE (TPR) METHOD - Aprilia Riyana Putri (Universitas Islam Nahdlatul Ulama Jepara, 2016)
Teaching English for young learners needs some good methods because English here is as a second or foreign language. Young learners do not practice to make communication using English with their families or people around them. So, it will be difficult to teach them if the teacher only use a common way. As an English teacher, choosing good method to make their students learning English Easily is a must. And Total Physical Response is one of an alternative good method for teaching English for young Learners. It can help young learners to memorize some commands or some vocabularies easily through use their physical movement. The students will not only learnable but also interesting and enjoyable. Total Physical Response is very good method for Kinesthetic learner who need to be active in the classroom. This method tries to introduce the language skill in an action and the English teacher has three responsibilities: as an instructor, as a role model, and an action supervisor until they are ready to imitate what the teacher said and did. This method is good for improving students listening and speaking skills.